New Promoters for Metabolic Engineering of Ashbya gossypii - Gloria Muñoz-Fernández (MDPI AG, 2021)
Ashbya gossypii is a filamentous fungus that is currently exploited for the industrial production of riboflavin. In addition, metabolically engineered strains of A. gossypii have also been described as valuable biocatalysts for the production of different metabolites such as folic acid, nucleosides, and biolipids. Hence, bioproduction in A. gossypii relies on the availability of well-performing gene expression systems both for endogenous and heterologous genes. In this regard, the identification of novel promoters, which are critical elements for gene expression, decisively helps to expand the A. gossypii molecular toolbox. In this work, we present an adaptation of the Dual Luciferase Reporter (DLR) Assay for promoter analysis in A. gossypii using integrative cassettes. We demonstrate the efficiency of the analysis through the identification of 10 new promoters with different features, including carbon source-regulatable abilities, that will highly improve the gene expression platforms used in A. gossypii. Three novel strong promoters (PCCW12, PSED1, and PTSA1) and seven medium/weak promoters (PHSP26, PAGL366C, PTMA10, PCWP1, PAFR038W, PPFS1, and PCDA2) are presented. The functionality of the promoters was further evaluated both for the overexpression and for the underexpression of the A. gossypii MSN2 gene, which induced significant changes in the sporulation ability of the mutant strains.